(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Changes in technology made a paradigm shift in the banking industry. Technology itself created its world in the globe of human beings. Internet banking is a service that allows customers to perform a wide range of financial services through a banks website. With the rapid diffusion of the Internet, web-based banking has become an alternative channel to provide banking services and products. Due to the deepness of technology in the service sector, there is a shift from the traditional service quality to electronic service quality (ESQ) in order to fit the Internet banking strategy. The aim of the paper is to rank and prioritize the Internet Banking Service Quality dimensions according to customers relevant importance from both bank sectors namely, private and public banks using Analytic Hierarchy Process (AHP) model, which is a structured technique for organizing and analyzing complex decisions. AHP has been seen as a high potential decision support tool in banking industry.